Wykorzystanie Zintegrowanego Programu Operacyjnego Rozwoju Regionalnego w województwie warmińsko-mazurskim - Czeszejko-Sochacka, Małgorzata; Wojarska, Magdalena (Making Use of Integrated Regional Operational Programme in Warmia and Mazury Voivodship, 2007)
The article shows the making use of Integrated Regional Operational Programme in Warmia and Mazury region. The data concern the period of Poland's European Union access by the end of the year 2005. In the studied period of time the value of signed agreements reached over 50% of available financial resources. Payment index was running at a considerably lower level. By the end of 2005 only 7% of contracted resources were paid off. The actions concerning road infrastructure and the action directed at microcompanies aroused the biggest interest. The lowest level of making use of contracted financial resources featured the actions concerning Priority 2, which were financed from the European Union Social Fund.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (15); 2007; nr 1166, s. 247-256